ANALISIS PENDAPATAN DAN TINGKAT KESEJAHTERAAN RUMAH TANGGA PETANI (KASUS PETANI PADI ORGANIK DAN ANORGANIK DI KECAMATAN PRINGSEWU DAN KECAMATAN PARDASUKA, KABUPATEN PRINGSEWU) - Triana, Ayu; Haryono, Dwi; Hasanuddin, Tubagus (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
This research aims to analyze the level of income and welfare of organic and inorganic rice farmers households in Pringsewu and Pardasuka Sub-District. This research used a case study method in Pringsewu and Pardasuka Sub-District, Pringsewu Regency purposively with consideration that the area is a regional pioneer of organic rice farming in Lampung Province and has obtained SNI certification from the government. The total samples were 37 farmers consisted of 17 organic rice farmers and 20 inorganic rice farmers. The data were collected in April-June 2018 and analyzed by farm income analysis, household income analysis, and welfare analysis based on BPS’s criteria (2014). The results showed that the average household income of organic and inorganic rice farmers in Pringsewu and Pardasuka Sub-Districts are IDR 21,520,505.88 per year and IDR18,785,344.38 per year. Based on BPS’s criteria, as many as 88.24% and 70% households of organic and inorganic rice farmers are included in the already prosperous category. Key words: household welfare, inorganic rice, income, organic rice